Application of Behavioral Counseling with Modeling Techniques and Social Skill to Improve Self Change - Ni Nyoman Sri Agustini Andayani; I Ketut Dharsana; Kadek Suranata (Department of Guidance and Counseling, FIP, Undiksha, 2020)
The purpose of this study was to improve the Self Change character of SMK Negeri 3 Denpasar Students. The low character of self-change of students is very interesting to be discussed and disclosed in a research study. This type of research is Experimental Research, with the design of pretest-group control group design. This research population is all class X of SMK Negeri 3 Denpasar. A sample of 102 students was taken randomly from the class and from the results of the distribution of self-change questionnaires, which were calculated using the T formula. The results of modeling techniques and social skills techniques showed that social skills techniques were effective in increasing self-change characteristics, while Modeling techniques were not effective change. This result is evidenced by the value of Fcount obtained at 29.944 and Ftable of 5.29. Compared to the value of Fcount with Ftable it is found that Fcount> Ftable with a significance level (p)> 0.01, it can be concluded that there are differences in the effectiveness of behavioral counseling between modeling techniques with Skill techniques Social to self change